Development of a Lagrangian meshless flow solver based on the Moving Particle Semi-implicit (MPS) method - Ng K.C.; Ng Y.L.; Yusoff M.Z. (Institute of Physics Publishing, 2023)
This paper discusses on the development of a meshless flow solver based on the Lagrangian particle method. The differential operators are discretised by using the particle interaction models proposed in the numerical framework of the Moving Particle Semi-implicit (MPS) technique. The MPS method is attractive from the viewpoint of no mesh is required and fluid is purely represented by points (the virtue of meshless algorithm). Some flow applications attempted by the current meshless solver will be shown and results are compared with the published experimental data. Published under licence by IOP Publishing Ltd.